Agricultural entrepreneurs in West Africa - (:unkn) unknown (My University, 2024)
This article focuses on the characteristics of West African agricultural entrepreneurs, examining their profiles and projects based on a sample of Togolese and Beninese entrepreneurs. The results show that millennials from non-agricultural backgrounds systematically settled outside the family framework, and that West African agricultural entrepreneurship involves the ex-nihilo creation of an agro-economic entity, given the region's specific context.
Keywords: African Research